Gambaran Penilaian Derajat Ulkus Diabetikum Menggunakan Klasifikasi Meggitt–Wagner dan SINBAD: Overview of Diabetic Ulcer Severity Assessment Using the Meggitt–Wagner and SINBAD Classifications - Alifia Wahyu Ardiyanti; suyanto; Mohammad Arifin Noor (Jurnal Keperawatan Berbudaya Sehat, 2026)
Assessing the severity of diabetic ulcers is crucial for determining clinical management and patient prognosis. This quantitative, cross-sectional study aimed to evaluate ulcer severity profiles using the Meggitt–Wagner and SINBAD classifications in type 2 diabetes mellitus (DM) patients. A total of 190 respondents were selected via purposive sampling, with a majority being male (50.5%) and working as housewives (51.1%). According to the Meggitt–Wagner classification, most respondents fell into the severe (47.4%) and moderate (43.7%) categories. Meanwhile, the SINBAD instrument classified patients predominantly into high (45.8%) and moderate (40.5%) categories. These findings indicate discrepancies in wound mapping distribution; Meggitt–Wagner emphasizes macro-anatomical aspects (wound depth and infection/gangrene), whereas SINBAD offers a more comprehensive evaluation by integrating broader physiological factors such as ischemia and neuropathy. In conclusion, the majority of patients presented with complex wound conditions requiring multidimensional management.